THE THEME OF LONELINESS IN THE LYRICS OF I. BRODSKY - Regina Fakhrutdinova (Modern American Journals, 2025)
The article examines the theme of loneliness in the lyrics of Joseph Brodsky as one of the key ones in his work. Particular attention is paid to the philosophical and existential dimension of loneliness, which acts for the poet not only as a form of internal state, but also as a way of understanding the world and himself. Using the example of the poems "Pilgrims" and "Fifth Anniversary", it is analyzed how loneliness is associated with the motives of wandering, exile, the passage of time and mortality. The work uses interpretations of modern literary scholars, which allows us to more deeply reveal the specifics of Brodsky's artistic world and his attitude to the metaphysical questions of human existence.
Keywords: Loneliness, lyrics, philosophy, existential approach.